Effectiveness of Preoperative Antiseptic Preparation in Transnasal Skull Base Surgery: A Randomized Three-Arm Controlled Trial - Ajlan, Abdulrazag; Alatar, Abdullah; Abdulqader, Sarah Bin; Alqurashi, Ashwag; Basindwah, Sarah; Farrash, Faisal; Aldhwaihy, Lolo; Elahi, Basim M. Noor; Alrasheed, Abdulaziz S.; Alqahtani, Abdulaziz; Alroqi, Ahmad; Alokby, Ghassan; Alzhrani, Gmaan; Alromaih, Saud; Bafaquh, Mohammed; Alhammad, Othman; Alobaid, Abdullah; AlFawwaz, Fahad; Alsaleh, Saad (Journal of Neurological Surgery Part B: Skull Base, 2024)
Transnasal skull base surgery is a complex and invasive procedure that involves the use of preoperative antiseptic preparations. However, evidence supporting their use in preventing postoperative infectious complications is limited. The aim of this study is to assess the efficacy of preoperative antiseptic techniques in reducing postoperative infectious complications within 30 days of surgery.A multicenter, prospective, randomized, single-blind, three-arm trial was conducted from February 2019 to October 2021. Participants were randomized to either of three antiseptic preparation techniques: external 0.9% NaCl nasal preparation, external 0.05% chlorhexidine gluconate, or intranasal irrigation with 80 mg of gentamicin added to 1,000 mL of 0.9% NaCl plus external nasal preparation with chlorhexidine gluconate 0.05%. A total of 130 adults with skull base pathologies were randomized; 12 were excluded before randomization for failure to meet the inclusion criteria (n = 9) or refusal to participate (n = 3). We excluded patients with evidence of infection adjacent to the surgical site, allergies to preparation methods, those who underwent craniotomy during the same admission, and pediatric patients.The mean age of the participants was 43.26 ± 14.45 years. Nine patients developed postoperative infections (meningitis, n = 8; sinusitis, n = 2). Among the factors studied, length of surgery (p = 0.002), perioperative cerebrospinal fluid (CSF) diversion (p = 0.01), chordoma (p = 0.004), extended approach (p = 0.026), and postoperative CSF leak (p = 0.025) were significantly associated with postoperative infections. There were no clinically meaningful or significant differences in the studied intervention groups regarding postoperative infectious complications.Preoperative antiseptic techniques failed to prefer one application to prevent postoperative infectious complications in patients who underwent endoscopic transnasal skull base surgery.
Keywords: antisepsis; skull base; sinusitis; meningitis